GAME EDUKASI BAHASA JEPANG MENGGUNAKAN ALGORITMA SUFFLE RANDOM BERBASIS ANDROID - Widia Sari Arezda Purba; Yuyun Dwi Lestari2; Yessi Fitri Annisah Lubis (SNASTIKOM, 2022)
Games are widely used as a learning medium for children so that they are not boring and can create an effectiveand interesting atmosphere. In the field of education, games are used as a forum for games to hone thinking andmemory in the learning process. The use of games in the learning process involving computers can increaseachievement and learning motivation. One of them is games with educational genres that can have a pleasantimpact on learning and games are useful because they have good visualizations and are not boring. This researchutilizes Japanese language education games to be a solution to the problem of difficulty in learning Japanese bythe Indonesian people due to differences in accent and cultural diversity. This educational game is built usingunity 3D software, where this research will aim to produce an android-based Japanese language education gameand implement a random suffle algorithm on the question feature. where the game will display random questionsto hone memory in the game.